2018
DOI: 10.1186/s12890-018-0743-0
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of allergic bronchopulmonary aspergillosis after adjunctive surgery for aspergilloma: a case report with long-term follow-up

Abstract: BackgroundCoexistence of aspergilloma and allergic bronchopulmonary aspergillosis (ABPA) has rarely been reported. Although the treatment for ABPA includes administration of corticosteroids and antifungal agents, little is known about the treatment for coexisting aspergilloma and ABPA. Furthermore, the impact of surgical resection for aspergilloma on ABPA is not fully understood. Here, we present an interesting case of recurrent ABPA with long-term follow-up after surgical resection of aspergilloma.Case presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Eosinophilic granulomatosis with vasculitis (previously referred to as Churg‐Strauss syndrome) is a very rare disorder characterized by nodules surrounding blood vessels that can be found in association with severe asthma, and it does not resemble the EG described here. The only syndrome in humans with a presentation somewhat similar to that of EG in dogs described here is aspergilloma, a noninvasive intra‐airway fungal infection treated with itraconazole or surgical excision . It is often found in association with bronchiectasis and also can be found with ABPA .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Eosinophilic granulomatosis with vasculitis (previously referred to as Churg‐Strauss syndrome) is a very rare disorder characterized by nodules surrounding blood vessels that can be found in association with severe asthma, and it does not resemble the EG described here. The only syndrome in humans with a presentation somewhat similar to that of EG in dogs described here is aspergilloma, a noninvasive intra‐airway fungal infection treated with itraconazole or surgical excision . It is often found in association with bronchiectasis and also can be found with ABPA .…”
Section: Discussionmentioning
confidence: 58%
“…The only syndrome in humans with a presentation somewhat similar to that of EG in dogs described here is aspergilloma, a noninvasive intra-airway fungal infection treated with itraconazole or surgical excision. 17,18 It is often found in association with bronchiectasis and also can be found with ABPA. 19,20 However, in our study, all dogs with EG tested for fungal infection were negative on culture or histopathology, indicating a lack of similarity to this condition in humans.…”
Section: Discussionmentioning
confidence: 99%
“…A. Maertens et al [8] indicate a high frequency of negative cultural results, which significantly complicates the differential diagnosis. Also, identification of galactomannan antigen in serum and bronchoalveolar lavage samples [12] and Aspergillusspecific IgE, is recommended for diagnosis of aspergillosis [13]. And for the diagnosis of endobronchial aspergilloma, which is diagnosed in various diseases (cancer with metastases, TB, bronchiolitis, etc.…”
mentioning
confidence: 99%
“…Horiuchi K. et al [13] observed a clinical case of simultaneous course of allergic bronchiolegenic aspergillosis and aspergilloma in a patient, who had had TB in the past. Despite massive hormone and antifungal therapy, the patient continued to have respiratory symptoms, which were the reason of lobectomy of the upper lobe of the right lung, where aspergilloma was localized.…”
mentioning
confidence: 99%